Isolation, Detection, and Characterization of Enterotoxigenic Bacteroides fragilis in Clinical Samples - Fathi, Payam (Open Microbiol J, 2016)
Bacteroides fragilis is an extensively studied anaerobic bacterium comprising the normal flora of the human gut. B. fragilis is known to be one of the most commonly isolated species from clinical samples and has been shown to cause a wide range of pathologies in humans [1, 2]. As an opportunistic pathogen B. fragilis can cause abscess formation and bacteremia [2]. Additionally in its enterotoxigenic form, B. fragilis is a known cause of diarrheal illness, is associated with inflammatory bowel disease, and has been recently characterized in patients with colon cancer [3 - 5]. As research in the field of the gut microbiome continues to expand at an ever increasing rate due to advances in the availability of next generation sequencing and analysis tools it is important to outline various molecular methods that can be employed in quickly detecting and isolating relevant strains of B. fragilis. This review outlines methods that are routinely employed in the isolation and detection of B. fragilis, with an emphasis on characterizing enterotoxigenic B. fragilis (ETBF) strains.